Overexpression of miR-210-3p Impairs Extravillous Trophoblast Functions Associated with Uterine Spiral Artery Remodeling - Heyam Hayder (International Journal of Molecular Sciences, 2021)
Hsa-miR-210-3p has been reported to be upregulated in preeclampsia (PE); however, the functions of miR-210-3p in placental development are not fully understood, and, consequently, miR-210-3p’s role in the pathogenesis of PE is still under investigation. In this study, we found that overexpression of miR-210-3p reduced trophoblast migration and invasion, extravillous trophoblast (EVT) outgrowth in first trimester explants, expression of endovascular trophoblast (enEVT) markers and the ability of trophoblast to form endothelial-like networks. In addition, miR-210-3p overexpression significantly downregulated the mRNA levels of interleukin-1B and -8, as well as CXC motif ligand 1. These cytokines have been suggested to play a role in EVT invasion and the recruitment of immune cells to the spiral artery remodeling sites. We also showed that caudal-related homeobox transcription factor 2 (CDX2) is targeted by miR-210-3p and that CDX2 downregulation mimicked the observed effects of miR-210-3p upregulation in trophoblasts. These findings suggest that miR-210-3p may play a role in regulating events associated with enEVT functions and its overexpression could impair spiral artery remodeling, thereby contributing to PE.